Blended Lives: ICT Talk among Vulnerable Young People in Finland. (May 2016) - Granholm, Camilla
This article presents a qualitative study of ICT use among Finnish young people attending training programmes for youth outside employment and education. The data come from six focus group interviews and three individual interviews, as well as a single focus group interview with involved supervisors. The data was analyzed using McQuail's (1983) theory regarding the motives for individual media use. The results show that the young people use ICT primarily for entertainment, but their use is diverse. Young people choose the tools and dimensions for interaction that best fulfill their needs, blending together ingredients from both online and offline sources. Unlike previous research, young people in this study stated that they prefer talking to someone face-to-face about severe (health-related or emotional) problems. If social and youth services want to meet young people on their own terms, both online and offline services are needed.